PARTISIPASI POLITIK MASYARAKAT PEDESAAN DALAM PEMILIHAN GUBERNUR JAWA TENGAB TAHUN 2008 (Studi Kasus mengenai Partisipasi Politik Masyarakat Pedesaan di Kecamatan Karanggede, Boyolali dalam Pilgub Jateng 2008) - Wijaya, Sri Herwindya Baskara (Jurnal The Messenger, 2009)
Every citizen has interest and preference on who should command him/her andon the public policy.  The directly election of local leader is part of citizen contribution to the public policy corresponding to the Act No. 32 of 2004 about Local Government. That the governor and vice governor position is not based on the election mechanism by DPRD like the previous  age.  Thus, the society   is political  participation  has a very important   role here. Based on the result of research shows  that generally,  the rural society  in subdistrict  Karanggede  Boyolali  has  the   lower participation  level  in the Central Java's Governor of 2008.